Intramyocardial haemorrhage and prognosis after ST-elevation myocardial infarction. (24th August 2018) - Reinstadler, Sebastian J; Stiermaier, Thomas; Reindl, Martin; Feistritzer, Hans-Josef; Fuernau, Georg; Eitel, Charlotte; Desch, Steffen; Klug, Gert; Thiele, Holger; Metzler, Bernhard; Eitel, Ingo
Abstract: Aims: To evaluate the prognostic value of intramyocardial haemorrhage (IMH) depicted by T2* imaging for risk stratification in ST-elevation myocardial infarction (STEMI) patients in comparison with established cardiac magnetic resonance (CMR) prognosis markers. Methods and results: This multicentre study enrolled 264 patients reperfused within 12 h after symptom onset. CMR was performed within the first week after STEMI to assess left ventricular function and infarct characteristics including IMH. The primary endpoint was a composite of death, reinfarction, and new congestive heart failure (major adverse cardiac events, MACE) at 12 months. MACE occurred in 19 patients (7.2%) showing a higher prevalence of IMH when compared with patients without MACE (47% vs. 21%, P = 0.008). The presence of IMH ( n = 60, 23%) was independently associated with MACE after adjusting for clinical risk factors [hazard ratio 2.7, 95% confidence intervals (CIs) 1.1–6.6; P = 0.032] or other CMR prognosis markers (hazard ratio 3.1, 95% CI 1.2–7.7; P = 0.013). The addition of IMH to a model of prognostic CMR parameters (ejection fraction, infarct size, and microvascular obstruction) led to net reclassification improvement of 0.42 (95% CI 0.11–0.73, P = 0.009). Conclusion: IMH assessed by T2* imaging may provide prognostic information that is incremental to other CMR markers of infarct severity and classical clinical risk factors. IMH could therefore be relevant as an important prognostic measure as well as therapeutic target when caring for patients after STEMI.